Pengaruh Nanoselulosa dari Pelepah Nipah sebagai Filler terhadap Sifat Bioplastik Polivinil Alkohol - Sunardi Sunardi; Nur Firda Trianda; Utami Irawati (Justek : Jurnal Sains dan Teknologi, 2020)
In this research, the synthesis of nanocellulose from Nypa fruticans fronds as a filler of polyvinyl alcohol-based bioplastic has been carried out. Nanocellulose synthesis was carried out using sulfuric acid hydrolysis process with a concentration of 30% and the results were analyzed using a Particle Size Analyzer. The effect of addition of the amount of nanocellulose on bioplastics from polyvinyl alcohol such as moisture content, thickness, transparency, vapor transmission rate, solubility and functional group analysis using FTIR have been evaluated. The results showed that the nanocellulose from Nypa fruticans fronds had a diameter below 600 nm. The addition of nanocellulose with a concentration of 0.2%; 0.4% and 0.6% into the polyvinyl alcohol bioplastic can increase the thickness and transparency of the bioplastic, and reduce the water vapor transmission rate. However, the addition of nanocellulose in this range did not significantly affect the water content and the solubility of bioplastics in water.